2000
DOI: 10.1002/(sici)1098-2752(2000)20:2<85::aid-micr7>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of muscle flap sensibility by evoked potentials in the rat

Abstract: This study investigated whether the sensory-to-motor reinervation of the muscle flap provides a better sensory recovery of an overlying skin graft. Fifty-four animals were studied in three groups of 18 rats each: group I (control): 1 cm of the gastrocnemius muscle motor nerve was excised and no repair was performed; group II (motor-to-motor repair): the motor nerve of the gastrocnemius flap was transected and repaired; group III (sensory-to-motor repair): the motor nerve of the gastrocnemius muscle and sural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…This model was designed for coverage of the facial structure, not for the functional transfer of muscle, which is really needed in severely burned patients. Our previous experience using large skin flaps for coverage of defects showed that flaps become sensate by the ingrowth of superficial nerves from surroundings (22). We have observed the same effect in this facial allograft study, in which large skin allografts become sensate as confirmed by the pin-prick test after 6 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…This model was designed for coverage of the facial structure, not for the functional transfer of muscle, which is really needed in severely burned patients. Our previous experience using large skin flaps for coverage of defects showed that flaps become sensate by the ingrowth of superficial nerves from surroundings (22). We have observed the same effect in this facial allograft study, in which large skin allografts become sensate as confirmed by the pin-prick test after 6 weeks.…”
Section: Discussionsupporting
confidence: 82%
“…This created a sensory-to-motor reinnervation, which has previously been shown to prevent muscle atrophy in animal studies. 15 At the three-month follow-up examinations, no significant atrophy was detected.…”
Section: Discussionmentioning
confidence: 94%
“…The recovery of sensation in microvascular free flaps is somewhat more variable and depends on whether the flaps are neurotized (6)(7)(8), the site of the recipient bed (5) and the time period following the procedure (6). Also, there is evidence to suggest that there may be heterogeneity in the pattern of sensory recovery in those flaps that regain sensation.…”
Section: Discussionmentioning
confidence: 99%